Effectiveness of fish monitoring programs in hydropower plant reservoirs - Fontes, Raquel Coelho Loures (2019)
Fish monitoring programs in hydropower plant reservoirs require significant investment of time, money and human resources for its implementation and maintenance. However, are these resources being applied in the best way and generating satisfactory results? With this in mind, this study presents analysis of data from fish monitoring performed in reservoirs using gill nets, aiming to detect temporal and spatial patterns of fish diversity (Chapters 1 and 2). This study also aimed to define a set of guidelines to improve fish monitoring programs effectiveness in hydropower plant reservoirs in Brazil (Chapter 3). In order to meet the first objective, in the first two chapters, data from more than 20 years of fish monitoring in the Araguari cascade reservoirs (Nova Ponte, Miranda, Amador Aguiar I and Amador Aguiar II). Itumbiara reservoir, on the Paranaíba River, was included in the analysis because it impounds the Araguari River mouth. Over time, in these reservoirs, there was a clear tendency for native species and migratory species to decline and non-native fish species to increase. The results also indicated a longitudinal dissimilarity gradient of fish assemblages over time , as the distance between the reservoirs increases in upstream-downstream direction. Considering the lotic environments that alternate between the reservoirs in the cascade, we observed a greater species loss in reservoirs, suggesting that the transformation from a lotic environment into a lentic had greater impact on fish assemblages than the flow regulation of the lotic remnants. The trends and patterns in fish diversity observed over time and in space, demonstrates that monitoring can be effective in providing important information on biodiversity changes. Nevertheless, several aspects ranging from planning, going through execution to analysis and management of monitoring data, must be carefully considered so that data quality, and consequently the conclusions from them, are not compromised. In Chapter 3, these aspects were considered and discussed after the characterization of fish monitoring activity in hydropower plant reservoirs. The characterization was the result of a survey (questionnaire) with several concessionaires of the Brazilian Electricity Sector. Finally, 10 guidelines that aim to improve monitoring programs management by the companies of the Sector were proposed. These guidelines were linked to a PDCA (plan-do-check-act) cycle designed to guide specific actions in each of the four stages of it. With the implementation of our suggested changes, the results will only be perceived in the medium-long term, so it is extremely important to start as soon as possible, to predict the continuity of actions and monitoring and, to constantly evaluate the programs. Thus, this study demonstrates and reinforces the importance that, for more robust results and more effective programs in what is proposed, long-term monitoring is necessary; analyzes that consider larger ge ographic scales, especially in cascade systems of reservoirs, greater scientific rigor in the planning of the sampling drawings of the monitoring and, therefore, in their analysis of data.